Highly-dispersed nickel nanoparticles decorated titanium dioxide nanotube array for enhanced solar light absorption - Chen, Jian; Zhou, Yingke; Li, Ruizhi; Wang, Xi; Chen, George Z. (Elsevier, 2019)
Honeycomb titanium dioxide nanotube array (TiO2-NTA) decorated by highly-dispersed nickel nanoparticles (Ni-NPs) has been grown under control on Ti foil by anodization and subsequent electrodeposition. The pore diameter and length of TiO2-NTA, and the size and quantity of Ni-NPs can be controlled via modulating the variables of the electrochemical processes. It has been found that the pretreatment of TiO2-NTA in the Cu(NO3)2 solution and further annealing at 450 °C in air could greatly improve the dispersion of the electrodeposited Ni-NPs. Absorption of the light in the solar spectrum from 300 to 2500 nm by the Ni-NPs@TiO2-NTA is as high as 96.83%, thanks to the co-effect of the light-trapping of TiO2-NTA and the plasmonic resonance of Ni-NPs. In the water heating experiment performed under an illuminating solar power density of ∼1 kW m−2 (AM 1.5), the ultimate temperature over 66 °C and an overall efficiency of 78.9% within 30 min were obtained, promising for applications in photothermal conversion and solar energy harvest.